Author Correction: Myeloperoxidase is not a good biomarker for preeclampsia prediction - Rocha-Penha, L. [UNESP]; Bettiol, H.; Barbieri, M. A.; Cardoso, V. C.; Cavalli, R. C.; Sandrim, V. C. [UNESP] (Springer Nature, 2018)
Te authors acknowledge the Conselho Nacional de Desenvolvimento Científco e Tecnológico (CNPq-Brazil), the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES-Brazil), and the Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP-Brazil) for fnancial help, as well as the team involved in BRISA study. should read: Te authors acknowledge the Conselho Nacional de Desenvolvimento Científco e Tecnológico (CNPq-Brazil; grant #2014-5/305587), the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES-Brazil), and the Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP-Brazil grants #2017/14546-6, #2015/20461-8 and #2008/53593-0) for financial help, as well as the team involved in BRISA study..